PEMIKIRAN IBNU SINA DALAM BIDANG FILSAFAT - Parlaungan, Parlaungan; Daulay, Haidar Putra; Dahlan, Zaini (Jurnal Bilqolam Pendidikan Islam, 2021)
The aims of this study are (1) to find out the biography of the Islamic philosopher, Ibn Sina. (2) To know the famous works of Ibn Sina. (3) To find out how the philosophical views of Ibn Sina. Ibn Sina's full name is Abu Ali Husayn bin Abdullah bin Hasan bin Ali bin Sina. He was born in the month of Safar 370 H or August-September 980 AD in Afsyanah, a small town in the current Uzbekistan region. He died in the city of Hamadan at the age of 58 to coincide in the year 428 AD or 1037 H. Ibn Sina has written a number of 276 works, both in the form of letters, books, and encyclopedias which he wrote during his short life. His most popular works are: First, Kitab Al-Qanun Fith Thib (Canon of Medicine). Second, the Book of Al-Juzah Ibn Sina Ath-Tibbiyah, Third, An-Najat, Fourth, Al-Isign wat-Tanbiat, Fifth, Al-Hikmat al-Masyriqiyyah. In the field of philosophy, Ibn Sina divides philosophy into three parts: (1) Philosophy of Emanation or Al-Faidh, (2) Philosophy of Being/Divinity and (3) Philosophy of Soul/Breath.